Collecting more than half the fluorescence photons from a single ion - Maiwald, Robert; Golla, Andrea; Fischer, Martin; Bader, Marianne; Heugel, Simon Tobias; Chalopin, Benoit; Sondermann, Markus; Leuchs, Gerd (Physical Review A, 2012)
We demonstrate the trapping of a single ion in the focus of a deep parabolic mirror that covers 81% of the solid angle surrounding the ion. Accounting for the reflectivity of the mirror we infer a photon collection efficiency of 54.8% for our setup. The underlying experimentally detected maximum fluorescence rate is 1.91×106 s 1 from a single 174Yb ion, mainly limited by the quantum efficiency of our photon detector. Besides the high collection efficiency, the integration of an ion trap into a parabolic mirror is a key ingredient for efficient coupling of light to a single ion in free space. © 2012 American Physical Society.

Efficient coupling to an optical resonator by exploiting time-reversal symmetry - Bader, Marianne; Heugel, Simon Tobias; Chekhov, Alexander; Sondermann, Markus; Leuchs, Gerd (New Journal of Physics, 2013)
The interaction of a cavity with an external field is symmetric under time reversal. Thus, coupling to a resonator is most efficient when the incident light is the time reversed version of a free cavity decay, i.e. when it has a rising exponential shape matching the cavity lifetime. For light entering the cavity from only one side, the maximally achievable coupling efficiency is limited by the choice of the cavity mirrors' reflectivities. Such an empty-cavity experiment serves also as a model system for single-photon single-atom absorption dynamics. We present experiments coupling exponentially rising pulses to a cavity system which allows for high coupling efficiencies. The influence of the time constant of the rising exponential is investigated as well as the effect of a finite pulse duration. We demonstrate coupling 94% of the incident TEM mode into the resonator. © IOP Publishing and Deutsche Physikalische Gesellschaft.

Efficient saturation of an ion in free space - Fischer, Martin; Bader, Marianne; Maiwald, Robert; Golla, Andrea; Sondermann, Markus; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2014)
We report on the demonstration of a light-matter interface coupling light to a single (Formula presented.) ion in free space. The interface is realized through a parabolic mirror partially surrounding the ion. It transforms a Laguerre–Gaussian beam into a linear dipole wave converging at the mirror’s focus. By measuring the non-linear response of the atomic transition, we deduce the power required for reaching an upper-level population of (Formula presented.) to be (Formula presented.) at half linewidth detuning from the atomic resonance. Performing this measurement while scanning the ion through the focus provides a map of the focal intensity distribution. From the measured power, we infer a coupling efficiency of (Formula presented.) on the linear dipole transition when illuminating from half solid angle, being among the best coupling efficiencies reported for a single atom in free space.

Focusing characteristics of a 4pi parabolic mirror light-matter interface - Alber, Lucas; Fischer, Martin; Bader, Marianne; Mantel, Klaus; Sondermann, Markus; Leuchs, Gerd (arXiv, 2016)

Focusing characteristics of a 4π parabolic mirror light-matter interface - Alber, Lucas; Fischer, Martin; Bader, Marianne; Mantel, Klaus; Sondermann, Markus; Leuchs, Gerd (Journal of the European Optical Society: Rapid Publications, 2017)

Generation of a wave packet tailored to efficient free space excitation of a single atom - Golla, Andrea; Chalopin, Benoit; Bader, Marianne; Harder, Irina; Mantel, Klaus; Maiwald, Robert; Lindlein, Norbert; Sondermann, Markus; Leuchs, Gerd (European Physical Journal D, 2012)
We demonstrate the generation of an optical dipole wave suitable for the process of efficiently coupling single quanta of light and matter in free space. We employ a parabolic mirror for the conversion of a transverse beam mode to a focused dipole wave and show the required spatial and temporal shaping of the mode incident onto the mirror. The results include a proof of principle correction of the parabolic mirror's aberrations. For the application of exciting an atom with a single photon pulse, we demonstrate the creation of a suitable temporal pulse envelope. We infer coupling strengths of 89% and success probabilities of up to 87% for the application of exciting a single atom for the current experimental parameters. © EDP Sciences, Società Italiana di Fisica, Springer-Verlag 2012.